2005
DOI: 10.1029/2005gl022685
|View full text |Cite
|
Sign up to set email alerts
|

Solar influence on the Indian summer monsoon during the Holocene

Abstract: [1] The large (8%) changes in the past seasonal insolation have a well-documented influence on the Indian summer monsoon. However, the effect of the small (<1%) decade to century scale solar variability is less certain. Evidence is emerging that Earth's climate is sensitive to small changes in solar output on centennial time scale during the Holocene. Comparison of a recently published proxy record for sunspot activity with our newly-revised higher-resolution record of the Indian summer monsoon winds reveals m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
195
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(224 citation statements)
references
References 36 publications
22
195
2
Order By: Relevance
“…These results are consistent with other Holocene records in and around the Arabian Sea (Fleitmann et al 2003;Gupta et al 2005) and Andaman Sea (Rashid et al 2007).…”
supporting
confidence: 82%
“…These results are consistent with other Holocene records in and around the Arabian Sea (Fleitmann et al 2003;Gupta et al 2005) and Andaman Sea (Rashid et al 2007).…”
supporting
confidence: 82%
“…The H5 record suggests a decreasing trend of ISM strength, which is supported by most of the other well-dated and high-resolution ISM records in ISM margin areas Sun et al, 2016;Xu et al, 2012Xu et al, , 2013a. A previous study has indicated that solar irradiance has a significant influence on the ISM on multi-decadal to centennial timescales, and that reduced solar output is correlated with weaker ISM winds (Gupta et al, 2005). However, solar irradiance has increased since 1810-1820 CE (Bard et al, 2000;Lean et al, 1995) and therefore it cannot be the main reason for the weaker ISM since 1820 CE.…”
Section: Interannual Variability Of the Ism Inferred From The Regionamentioning
confidence: 54%
“…Clemens et al, 2003;, and solar activities have been hypothesized as the driver of a 1500-yr cycle in Holocene monsoon dynamics (e.g. Gupta et al, 2005;. However, the patterns and causes of decadal-centennial variability are not well understood due to the limits in the length of observational records and relatively coarse resolution of proxy data.…”
Section: Introductionmentioning
confidence: 99%